1991
DOI: 10.1111/j.1365-2265.1991.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle and body composition after discontinuation of growth hormone treatment in growth hormone deficient young adults*

Abstract: Although the changes measured were relatively small they suggest a role for GH in the maintenance of muscle integrity and body composition in the young adult with growth hormone deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 19 publications
(9 reference statements)
3
44
0
2
Order By: Relevance
“…Studies, in which young adults with GH therapy in childhood/adolescence have been retested, have shown that some, but not all, of these patients have persisting severe GHD according to the diagnostic criteria set in adult life (12,13). Discontinuing GH therapy at final height in adolescents with severe GHD into adult life produces similar clinical characteristics as those observed in other groups of adult patients with GHD (14)(15)(16)(17)(18)(19)(20)(21)(22). Quality of life may, however, be less affected by GH discontinuation in this patient group (20).…”
Section: Introductionmentioning
confidence: 54%
“…Studies, in which young adults with GH therapy in childhood/adolescence have been retested, have shown that some, but not all, of these patients have persisting severe GHD according to the diagnostic criteria set in adult life (12,13). Discontinuing GH therapy at final height in adolescents with severe GHD into adult life produces similar clinical characteristics as those observed in other groups of adult patients with GHD (14)(15)(16)(17)(18)(19)(20)(21)(22). Quality of life may, however, be less affected by GH discontinuation in this patient group (20).…”
Section: Introductionmentioning
confidence: 54%
“…GH deficiency in adults is associated with diminished strength and a reduction in muscle force, secondary to both a reduction in muscle mass and a reduction in the contractile properties of muscle fibers and neural recruitment of fibers (36,37). Twelve months after withdrawal of GH therapy in young adults who were GH deficient, Rutherford et al reported a reduction in muscle strength, size, and fiber area (38). GH replacement, in GHdeficient adults, leads to an increase in muscle mass and muscle strength of the limb and girdle muscles (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…A massa e a força muscular aumentam gradativamente após o fechamento das cartilagens de crescimento, porquanto o pico de massa muscular ocorre entre os 20 e 30 anos de idade (8). A suspensão do tratamento com GH, quando o paciente com DGH atinge a estatura final, reduz a massa e a força muscular (5,(8)(9)(10), comprometendo a capacidade para a atividade física (11). Estas alterações são reversíveis com a reposição de GH (5,12).…”
Section: Manifestações Clínicas E Metabólicasunclassified
“…Estas alterações são reversíveis com a reposição de GH (5,12). A deficiência de GH aumenta o tecido adiposo, tanto em nível subcutâneo quanto em nível visceral (4)(5)(6)9). A reposição deste hormônio aumenta a lipólise, principalmente da gordura visceral (2,12), diminuindo o percentual de tecido adiposo nos portadores de DGH (12).…”
Section: Manifestações Clínicas E Metabólicasunclassified